The use of hydrofluoric acid as a surface treatment material on bond strength in repair system of lithium disilicate – Literature Review - Razalie, Ludwika Patricia; Ritonga, Putri Welda Utami; Syafrinani (Indonesian Journal of Prosthodontic, 2024)
Lithium disilicate is a glassy ceramic material that mimics the aesthetics and strength of natural tooth structure, making it very popular in recent years. Lithium disilicate has good flexural strength, translucency, and high mechanical strength of up to 360±60 MPa which is superior to feldspathic porcelain or leucite-reinforced glass ceramic. These excellent properties make it suitable for both anterior and posterior use. Naturally, ceramic materials are inherently brittle and tend to fracture easily in repetitive function. There are several methods of fracture treatment, one of which is repair. Composite resin is frequently used for ceramic repair as a simple and fast solution. The bond strength of ceramic repairs on lithium disilicate using hydrofluoric (HF) acid is higher compared to other methods. Hydrofluoric acid that has been used as a surface treatment for lithium disilicate is 4% and 5% HF acid. This article reviews the effect of HF as a surface treatment material on bonding strength between lithium disilicate and composite resin. The application of hydrofluoric acid in ceramic surface promotes the reaction with the glass matrix that contains silica and form hexafluorosilicates. This glass matrix is selectively removed and the crystalline structure is exposed. As a result, the surface of the ceramic becomes rough and this roughly etched surface helps to provide more surface energy prior to combining with the silane solution. Silane coupling agent forms a chemical covalent bond between silica on the lithium disilicate surface and composite resin. This bond will increase the micromechanical interlock. Keywords: lithium disilicate, surface treatment, hydrofluoric acid, bond strength